2015
DOI: 10.1007/s12601-015-0010-8
|View full text |Cite
|
Sign up to set email alerts
|

An overview of polybrominated diphenyl ethers (PBDEs) in the marine environment

Abstract:  Polybrominated diphenyl ethers (PBDEs), which are used extensively as brominated flame retardants, are found ubiquitously in marine environments worldwide. In this paper, we review all available data on the occurrence and trends of PBDEs in marine environments. PBDE levels in different marine environmental compartments vary from nanograms per gram to micrograms per gram, and differ widely, depending on the exposed species and the collection site. The PBDE congener profiles in biota, which are dominated by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(21 citation statements)
references
References 155 publications
0
18
1
Order By: Relevance
“…PBDE congener profiles in sediments are dominated by higher brominated congeners such as BDE-209 and DBDPE. This is different from profiles in biota samples, which are dominated by lower brominated congeners, such as BDE-47 and BDE-99 [34]. In marine sediments, BFRs were detected in Canada [35], San Francisco Bay, USA [36], Gulf of Lion, France [37], Northern Arabian Gulf [38], East Java Province, Indonesia [39], Goseong Bay, Korea [40], South China [41], and the Scheldt estuary, the Netherlands [42].…”
Section: Levels Of Pbdes and Nbfrs In Sediment And Soilmentioning
confidence: 63%
“…PBDE congener profiles in sediments are dominated by higher brominated congeners such as BDE-209 and DBDPE. This is different from profiles in biota samples, which are dominated by lower brominated congeners, such as BDE-47 and BDE-99 [34]. In marine sediments, BFRs were detected in Canada [35], San Francisco Bay, USA [36], Gulf of Lion, France [37], Northern Arabian Gulf [38], East Java Province, Indonesia [39], Goseong Bay, Korea [40], South China [41], and the Scheldt estuary, the Netherlands [42].…”
Section: Levels Of Pbdes and Nbfrs In Sediment And Soilmentioning
confidence: 63%
“…Table A2.2). PCBs 3200000 (fish) Jak et al (2000) PBDEs 2.3-7.6 (fish) 0.8-2.4 (porpoise) Lee and Kim (2015) 2.0-12.4 (harbour seal) Jenssen et al (2007) Internal effect concentrations and kinetic parameters (required for bioaccumulation modelling) are available to some extent for metals (Vijver en Van Gestel et al 2004;DeForest et al 2007;Van Kolck et al 2008). investigated the accumulation and biomagnification of PCB and PBDE congeners in blubber of harbour seals and harbour porpoises from the Southern North Sea.…”
Section: Bioaccumulationmentioning
confidence: 99%
“…As a "sink" for almost all types of pollutants, marine environment is the ultimate gathering place of PBDEs, which have been detected in seawater, sediments, and marine organisms (Jiang et al, 2019). And it was reported that PBDEs were several orders of magnitude higher in organisms than that in water because of their lipophilicity (Lee and Kim, 2015). Recently, a number of studies have focused on the in uence and toxicity of PBDEs on marine organisms at physiological, biochemical, and molecular levels.…”
Section: Introductionmentioning
confidence: 99%